Factors associated with weight loss response to GLP-1 analogues for obesity treatment: a retrospective cohort analysis - Nadia Khan; Jesse Bittman; Peter Squire; James Naude; Ali Zentner (BMJ Open)
Objectives The response to glucagon-like peptide-1 (GLP-1) analogues for weight loss varies significantly. We investigated the anthropometric, demographic and clinical characteristics associated with total body weight loss (TBWL) from subcutaneous GLP-1 analogue therapy in patients with obesity in a real-world setting.Design Retrospective cohort analysis.Setting An urban, multidisciplinary obesity community clinic in Vancouver, Canada, from November 2018 to April 2021.Participants 483 adults with a body mass index (BMI) of ≧30 kg/m2 who had filled a new prescription for subcutaneous semaglutide or liraglutide, with at least 6-month follow-up, were included (mean follow-up: 17.3 months). Individuals with prior bariatric surgery were excluded.Outcomes The primary outcome was the %TBWL over a mean follow-up period of 520 days. Participant’s TWBL was categorised as non-response (<5% TBWL), moderate response (5%–15% TBWL) or hyper-response (>15% TBWL).Results The average %TBWL in the cohort was 12.2%. Among the participants, 17.8% had a non-response, 48.4% had a moderate response and 33.8% had a hyper-response. In the multivariable regression analysis, being a woman was associated with hyper-response (adjusted OR 1.92, CI 1.01 to 3.65, p=0.048). Age, diabetes status, baseline BMI, being sedentary, anxiety and depression were not independently associated with TBWL in response to GLP-1 analogue therapy.Conclusions In a real-world setting, female sex was found to be associated with a hyper-response to GLP-1 analogue therapy for obesity management. Other clinical factors evaluated, including diabetes status, were not associated with the response. Future research should assess additional variables and support the development of novel biomarkers that are associated with weight loss response.